Floodplain mapping in Balanga City using hydrologic engineering center (HEC) models - Ines, Hale Jemimah S.
The simulation system for the assessment of flood flow is developed for Balanga City using hydrologic and hydraulic models simulated by HEC-HMS and HEC-RAS. Topography, river network, and actual rainfall data coming from rain gages within the city are used to generate flood hydrographs at various reaches of the channels. Assuming steady flow conditions, peak discharges from the hydrographs generated in HEC-HMS are utilized in HEC-RAS to determine water surface elevations. Results of the simulation of these surface profiles or water levels indicate the locations of flood-prone areas within the city, thus forecasting a flood and generating a floodplain map.